2017
DOI: 10.1097/j.pain.0000000000000951
|View full text |Cite
|
Sign up to set email alerts
|

Altered brain structure and function associated with sensory and affective components of classic trigeminal neuralgia

Abstract: Classic trigeminal neuralgia (CTN) is a chronic neuropathic pain state characterized by intense, piercing spasms of the orofacial region, and may be attributable to abnormal pain processing in the central nervous system. Our study investigated neuronal alterations using voxel-based morphometry (VBM), diffuse tensor imaging (DTI), and resting-state functional connectivity in 38 patients with CTN and 38 matched healthy controls. For voxel-based morphometry analyses, patients with CTN displayed gray matter volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 58 publications
3
90
0
Order By: Relevance
“…Our previous work together with other evidences (Hari et al ., ; Jarvelainen et al ., ; Ichikawa et al ., ; Tominaga et al ., ) further supported the role of the MI in the MNS. Moreover, several lines of research by investigating anatomical or functional connectivity have shown direct neural connections of somatosensory system to MI (Pavlides et al ., ; Shinoura et al ., ), inferior parietal cortex (Caspers et al ., ), and prefrontal cortex (Wang et al ., ). Thus, it was reasonable to postulate that the somatosensory cortex was also modulated by action modulation.…”
Section: Discussionmentioning
confidence: 97%
“…Our previous work together with other evidences (Hari et al ., ; Jarvelainen et al ., ; Ichikawa et al ., ; Tominaga et al ., ) further supported the role of the MI in the MNS. Moreover, several lines of research by investigating anatomical or functional connectivity have shown direct neural connections of somatosensory system to MI (Pavlides et al ., ; Shinoura et al ., ), inferior parietal cortex (Caspers et al ., ), and prefrontal cortex (Wang et al ., ). Thus, it was reasonable to postulate that the somatosensory cortex was also modulated by action modulation.…”
Section: Discussionmentioning
confidence: 97%
“…All subjects underwent a structured clinical interview and completed a brief psychological assessment. The Hamilton Anxiety Rating Scale (HAM-A) was used to evaluate anxiety symptoms (18,19), and the Hamilton Depression Rating Scale (HAM-D) measured feelings of depression (20). The obtained data were reviewed by a psychiatrist who was blinded to the experimental groups.…”
Section: Neuropsychological Assessmentmentioning
confidence: 99%
“…DTI allows investigating the macrostructure (e.g., the thickness and fiber density of major white matter fiber bundles) and microstructure of white matter (27). Using DTI, changes in white matter microstrucure were found in patients with various pain disorders, including musculoskeletal pain (28,29), fibromyalgia (30), trigeminal neuralgia (31)(32)(33), primary dysmenorrhea (34)(35)(36), and chronic neuropathic pain following spinal cord injury (37,38). Impaired white matter structure in chronic pain may be of con-siderable clinical importance because white matter disorder may be associated with cognitive deficits and may predict transition to chronic pain (39).…”
Section: Lishedmentioning
confidence: 99%